KUALITAS PELAYANAN PENGURUSAN SURAT IZIN MENGEMUDI DI SATUAN LALU LINTAS DI POLISI RESORT KABUPATEN BUOL - Sihira, Serly SB; Alam, Samsul; Satria (STISIPOL Mujahidin Buol, 2024)
The quality of the Driving License (SIM) processing service at the Buol Police and the output or results of the service can be explained through various service dimensions, as described in the SERVQUAL model, and the impact of the service on the community if managed properly, will provide many benefits for the community and institutions, including higher satisfaction, increased public trust, and improved institutional image. This research will be conducted at the Buol Police Resort located in Buol Regency. The research method used is qualitative with a descriptive approach, so that it only presents the actual situation at the research location, data collection techniques using observation, interviews, and documentation.The results of the study show the quality of the Driving License (SIM C) making service at the Buol Police Resort Traffic Unit Office. The study on the quality of service provision at the Buol Police Resort is focused on the following aspects: Tangible, Reliability, Responsiveness, Assurance, and Employment. It can be concluded that the services provided at the Buol Police Resort are good, but the quality of service is still lacking.